(untitled) (IPS Journal of Nutrition and Food Science, 2023)
Milk is one of the most important nutritional constituent of our diet because it is largely composed of proteins and along with vitamins and minerals. This present study was based on determining the amount of casein and lactose present in processed (Dano cool cow and Peak milk) and unprocessed milk (Cow and Goat milk) samples collected from Ogwashi-uku, Delta State. The casein content was analyzed using Kjeldahl method and lactose content was analyzed using Benedict’s Method. Results from this study shows that cow milk sample; an unprocessed form of milk has more lactose content (40.298%) than other forms of milk while Dano cool cow milk, a processed milk has more casein (23.93%) as compared to all other milk. High concentration of casein is more beneficial to health and high percentage of lactose do not poses no threat as it can be digested easily.